2021
DOI: 10.3390/su14010111
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sociodemographic Factors on Construction Fieldworkers’ Safety Risk Assessments

Abstract: Construction operations are hazardous, leading to thousands of accidents, injuries, and fatalities annually. Safety risk assessment (SRA) is a key component necessary to respond to hazards effectively. Individuals have different perceptions of the riskiness of construction hazards, and studies have shown that different sociodemographic factors among employees can alter their SRA skills. However, their role in the US construction industry has been understudied, and this analysis investigates this topic further.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…In terms of the impact of training on risk perception among employees, Chaswa et al (2020) and Ibrahim et al (2022) did not find a significant relationship. Eiris et al (2020) reached interesting conclusions, drawing attention not to the mere fact of undergoing occupational health and safety training by employees but to the quality of training and the training techniques used, which are, in their opinion, crucial.…”
Section: Literature Reviewmentioning
confidence: 72%
See 3 more Smart Citations
“…In terms of the impact of training on risk perception among employees, Chaswa et al (2020) and Ibrahim et al (2022) did not find a significant relationship. Eiris et al (2020) reached interesting conclusions, drawing attention not to the mere fact of undergoing occupational health and safety training by employees but to the quality of training and the training techniques used, which are, in their opinion, crucial.…”
Section: Literature Reviewmentioning
confidence: 72%
“…In the case of another demographic variable, i.e., age, Chaswa et al (2020) and Han et al (2019) demonstrated the impact of age on risk perception, with people aged 37-46 tending to ignore the risks associated with commonly encountered threats (Han et al, 2019). Wang et al (2019) and Ibrahim et al (2022) reached different conclusions, as according to their research results, all employees, regardless of their age, perceived the risk similarly. Inconclusive results were obtained by Meng and Chan (2020), as their research indicated that male employees' risk perception of workplace hazards increased with age, while among women, age had no significance in risk perception.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…The World Health and Safety Executive Report states that the construction industry is the most important industry responsible for high injury and fatality rates in both developing and developed countries [1][2][3]. The construction industry has contributed significantly to the economic growth in many countries.…”
Section: Introductionmentioning
confidence: 99%